Sequential electron transfer governs the UV-induced self-repair of DNA photolesions - Szabla, Rafał; Kruse, Holger; Stadlbauer, Petr; Šponer, Jiří; Sobolewski, Andrzej L (Chemical science, 2018)
Cyclobutane pyrimidine dimers (CpDs) are among the most common DNA lesions occurring due to the interaction with ultraviolet light. While photolyases have been well known as external factors repairing CpDs, the intrinsic self-repairing capabilities of the GAT[double bond, length as m-dash]T DNA sequence were discovered only recently and are still largely obscure. Here, we elucidate the mechanistic details of this self-repair process by means of MD simulations and QM/MM computations involving the algebraic diagrammatic construction to the second order [ADC(2)] method. We show that local UV-excitation of guanine may be followed by up to three subsequent electron transfers, which may eventually enable efficient CpD ring opening when the negative charge resides on the T[double bond, length as m-dash]T dimer. Consequently, the molecular mechanism of GAT[double bond, length as m-dash]T self-repair can be envisaged as sequential electron transfer (SET) occurring downhill along the slope of the S1 potential energy surface. Even though the general features of the SET mechanism are retained in both of the studied stacked conformers, our optimizations of different S1/S0 state crossings revealed minor differences which could influence their self-repair efficiencies. We expect that such assessment of the availability and efficiency of the SET process in other DNA oligomers could hint towards other sequences exhibiting similar photochemical properties. Such explorations will be particularly fascinating in the context of the origins of biomolecules on Earth, owing to the lack of external repairing factors in the Archean age.